Restorative justice in context: international practice and directions - Weitekamp, Elmar G. M.; Kerner, Hans-Jürgen (Routledge, 2011)
The shape of things to come : a framework for thinking about a restorative justice system / Daniel W. Van Ness -- Journey to belonging / Howard Zehr -- Restorative justice and the politics of decolonization / Chris Cunneen -- Justified criticism, misunderstanding, or important steps on the road to acceptance? / Martin Wright and Guy Masters -- From community to dominion : in search of social values for restorative justice / Lode Walgrave -- Deconstructing restoration : the promise of restorative justice / George Pavlich -- Restorative justice theory validation / Paul McCold and Ted Wachtel -- Restorative justice and the future of diversion and informal social control / Gordon Bazemore and Colleen McLeod -- Restorative conferencing for juveniles in the United States : prevalence, process and practice / Mara Schiff and Gordon Bazemore -- Restorative justice for children : in need of procedural safeguards and standards / Christian Eliaerts and Els Dumortier -- From the 'sword' to dialogue : towards a 'dialectic' basis for penal mediation / Grazia Mannozzi -- Punishment, guilt and spirit in restorative justice : an essay in legal and religious anthropology / Robert E. Mackay -- The role of shame, guilt and remorse in restorative justice processes for young people / Gabrielle Maxwell and Allison Morris -- Peacemaking and community harmony : lessons (and admonitions) from the Navajo peacemaking courts / L. Thomas Winfree Jr. -- From philosophical abstraction to restorative action, from senseless retribution to meaningful restitution : just deserts and restorative justice revisited / Ezzat A Fattah -- Restorative justice : present prospects and future directions / Elmar G.M. Weitekamp.